Influence of the key parameters on the dynamic behavior of the hydrogen absorption by LaNi5. (12th January 2017) - Chabane, D.; Harel, F.; Djerdir, A.; Ibrahim, M.; Candusso, D.; Elkedim, O.; Fenineche, N.
Abstract: The optimal design of hydride tanks is a major technological issue for the rapid development of this technology. In this paper, a two-dimensional model of a closed metal–hydrogen reactor is presented. The temperature and the pressure temporal evolutions within the reactor as a function of time are reported. In order to determine the parameters to optimize a fast kinetic and optimal heat exchange, the impact of the supply pressure, the porosity and the dynamic viscosity have been studied. The results show that the effect of these parameters are key-factors for an optimized tank design. Highlights: A hydrogen storage. Modeling the hydrogen absorption in the porous media. To develop two dimensional heat and mass transfer model for a packed bed metal hydride reactor. Use Comsol-Multi physics. To analyze the effect of certain parameters on the behavior of the tank.